MOTIF SAKURA WARNA ALAM PADA KAIN PANJANG - Nuri Ningsih Hidayati (Corak : Jurnal Seni Kriya, 2015)
In this world, many countries have a beautiful flower that became icons as well asDutch Tulip flowers but the author is more interested in Sakura flowers that are part of Japan.In addition to its beautiful Sakura has turned out to be an important symbol, which is oftenassociated denganperempuan, life, death, and also a symbol to express the bond betweenhuman beings, courage, sadness, and joy. No wonder if Sakura much admired for its beauty.Sakura has become a part that can not be separated in Japanese culture one of which can beseen when the cherry flowers bloom in spring. With an overview of all events of the floweringcherry created new innovations in work such as engineering, color, and a unique motif. Keywords : motif, sakura, natural color, long cloth  Di dunia ini banyak negara yang mempunyai bunga indah yang menjadi icon sepertihalnya Belanda dengan bunga Tulip akan tetapi penulis lebih tertarik pada bunga Sakura yangmerupakan bagian dari Jepang. Selain bentuknya yang indah ternyata Sakura mempunyai simbolpenting, yang kerap kali dikaitkan denganperempuan, kehidupan, kematian, serta jugamerupakan simbol untuk mengekspresikan ikatan antar manusia, keberanian, kesedihan, dankegembiraan. Tidak heran jika Sakura banyak dikagumi karena keindahannya. Sakura sudahmenjadi bagian yang tidak bisa dipisahkan dalam kebudayaan Jepang salah satunya bisa dilihatketika bunga Sakura mekar di musim semi. Dengan gambaran semua peristiwa mekarnya sakuratercipta inovasi baru dalam berkarya berupa teknik, warna, dan motif yang unik. Kata kunci: motif, sakura, warna alam, kain panjang